Estudio del disco circunestelar de estrellas Be del hemisferio norte galáctico a partir de un análisis espectroscópico en la banda L (2016)
In the various research topics in stellar variability, the Be stars are studied. They are considered as stars of spectral type B, whose spectra show or have shown once Balmer emission lines. They possess a very rapid rotation, leading to the generation of a circumstellar disk shaped envelope. These stars remain enigmatic objects, because the mechanisms that drive and regulate the disk dynamic remain under study. One way to explore that dynamics is to perform a spectroscopic analysis of the infrared emission lines of the Be star's disk using spectroscopic parameters such as equivalent widths (EW), integrated flux (F) and full width at half maximum (FWHM). In this paper new spectra are shown in the L-band (3µm-4µm) of four Be stars: 66 Ophiuchus, Omicron Herculis, Sheliak and ¿ Coronae Borealis, belonging to the northern galactic hemisphere. These spectra were obtained during the first half of 2014 with the CID-InSb spectrograph of the 2.1m telescope in San Pedro Martir Observatory (Institute of Astronomy at UNAM, Mexico). Reduction processes, wavelength calibration, telluric correction and flux calibration of the Infrared spectra are presented in this paper also. To develop such a spectroscopic analysis, it is used the IRAF (Image Reduction and Analysis Facility) software as a tool for processing. Specifically, the parameters F, EW and FWHM are used to obtain different ratios between spectral lines of Humphreys, Pfund and Brackett series, in order to analyze changes in the optical depth and density of the disks. Also, it is possible to relate FWHM of the Humphreys lines with the rotation speed of the disc regions where such lines are formed. Moreover, the stars of this work are classified according to the intensity of the emission lines of the above series. This classification is related to the optical depth of the envelopes in Be star disks. In addition, from the results, inferences about the evolutionary changes that could present the stars of this work are done. The results of this research confirm the usefulness of infrared spectra to understand some physical properties and evolution of circumstellar disks of Be stars. These results are also compared with those previously reported in the literature for Be stars of the southern galactic hemisphere, in order to confirm the ideas raised in these studies about disk density changes.